Spatial and quantitative mapping of glycolysis and hypoxia in glioblastoma as a predictor of radiotherapy response and sites of relapse. - Leimgruber, Antoine; Hickson, Kevin; Lee, Sze Ting; Gan, Hui K; Cher, Lawrence M; Sachinidis, John I; O'Keefe, Graeme J; Scott, Andrew M (European Journal of Nuclear Medicine & Molecular Imaging, 2020)
Introduction: Tumor hypoxia is a centerpiece of disease progression mechanisms such as neoangiogenesis or aggressive hypoxia-resistant malignant cells selection that impacts on radiotherapy strategies. Early identification of regions at risk for recurrence and prognostic-based classification of patients is a necessity to devise tailored therapeutic strategies. We developed an image-based algorithm to spatially map areas of aerobic and anaerobic glycolysis (Glyoxia). Methods: 18F-FDG and 18F-FMISO PET studies were used in the algorithm to produce DICOM-co-registered representations and maximum intensity projections combined with quantitative analysis of hypoxic volume (HV), hypoxic glycolytic volume (HGV), and anaerobic glycolytic volume (AGV) with CT/MRI co-registration. This was applied to a prospective clinical trial of 10 glioblastoma patients with post-operative, pre-radiotherapy, and early post-radiotherapy 18F-FDG and 18F-FMISO PET and MRI studies. Results: In the 10 glioblastoma patients (5M:5F; age range 51–69 years), 14/18 18F-FMISO PET studies showed detectable hypoxia. Seven patients survived to complete post-radiotherapy studies. The patient with the longest overall survival showed non-detectable hypoxia in both pre-radiotherapy and post-radiotherapy 18F-FMISO PET. The three patients with increased HV, HGV, and AGV volumes after radiotherapy showed 2.8 months mean progression-free interval vs. 5.9 months for the other 4 patients. These parameters correlated at that time point with progression-free interval. Parameters combining hypoxia and glycolytic information (i.e., HGV and AGV) showed more prominent variation than hypoxia-based information alone (HV). Glyoxia-generated images were consistent with disease relapse topology; in particular, one patient had distant relapse anticipated by HV, HGV, and AGV maps. Conclusion: Spatial mapping of aerobic and anaerobic glycolysis allows unique information on tumor metabolism and hypoxia to be evaluated with PET, providing a greater understanding of tumor biology and potential response to therapy.